2012
DOI: 10.1063/1.4768889
|View full text |Cite
|
Sign up to set email alerts
|

Oscillation dynamics of embolic microspheres in flows with red blood cell suspensions

Abstract: Why and how does collective red blood cells motion occur in the blood microcirculation? Phys. Fluids 24, 101901 (2012) Depletion layer formation in suspensions of elastic capsules in Newtonian and viscoelastic fluids Phys. Fluids 24, 061902 (2012) Separation of blood cells using hydrodynamic lift Appl. Phys. Lett. 100, 183701 (2012) A new laser Doppler flowmeter prototype for depth dependent monitoring of skin microcirculation Rev. Sci. Instrum. 83, 034302 (2012) Vesicle tumbling inhibited by inert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…These parameters will, in turn, affect bead mechanical properties [17] and deliverability via microcatheters. Furthermore, we have previously demonstrated that the fluid dynamics within the target vascular system can influence the flow behaviour of suspended embolic beads [33] and, ultimately, determine the spatial location of vascular occlusion sites [34]. The spatial location of embolic events has been observed to further depend on bead size and concentration in the embolic suspension, which was previously postulated by others but only qualitatively [35].…”
Section: Accepted M Manuscriptmentioning
confidence: 84%
“…These parameters will, in turn, affect bead mechanical properties [17] and deliverability via microcatheters. Furthermore, we have previously demonstrated that the fluid dynamics within the target vascular system can influence the flow behaviour of suspended embolic beads [33] and, ultimately, determine the spatial location of vascular occlusion sites [34]. The spatial location of embolic events has been observed to further depend on bead size and concentration in the embolic suspension, which was previously postulated by others but only qualitatively [35].…”
Section: Accepted M Manuscriptmentioning
confidence: 84%
“…The physicochemical properties of microsphere suspensions have also been associated with the miscibility and distribution within hemodynamic flow . It has been proposed that microspheres will track to the distribution of injected solutions in blood .…”
Section: Suspension Handling and Microcatheter Delivery Of Microsphmentioning
confidence: 99%
“…observed lateral oscillations of microspheres in pipe flow by microscopy that he referred to an increase of the hematocrit level, i.e. red blood cells 31 . They observed that these lateral oscillations contain higher harmonics of the rotational frequency 31 .…”
Section: Discussionmentioning
confidence: 99%
“…red blood cells 31 . They observed that these lateral oscillations contain higher harmonics of the rotational frequency 31 . Though the lateral oscillatory MM traces (cf.…”
Section: Discussionmentioning
confidence: 99%